2022
DOI: 10.1186/s12938-022-00998-5
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis of potential gastric cancer prognostic biomarker ITGBL1 associated with immune infiltration and epithelial–mesenchymal transition

Abstract: Background Integrin, beta-like 1 (ITGBL1) is involved in a variety of human malignancies. However, the information on the involvement of ITGBL1 in gastric carcinoma (GC) is limited. Hence, this study aimed further to explore the functions and mechanisms of ITGBL1 in GC. Methods First, multiple bioinformatics databases, including Oncomine, Tumor Immune Estimation Resource, UALCAN, and Kaplan–Meier Plotter, were used to predict the expression level a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…According to a bioinformatics analysis-based study, it was shown that the overexpression of ITGBL1 had an impact on the overall survival. 21 Anoikis resistance exhibits a strong correlation with the processes of metastasis and tumour growth. 22,23 Thus, the identification of crucial regulators responsible for conferring resistance to anoikis, as well as understanding the underlying mechanisms via which their dysregulation occurs, holds significant importance in cancer progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a bioinformatics analysis-based study, it was shown that the overexpression of ITGBL1 had an impact on the overall survival. 21 Anoikis resistance exhibits a strong correlation with the processes of metastasis and tumour growth. 22,23 Thus, the identification of crucial regulators responsible for conferring resistance to anoikis, as well as understanding the underlying mechanisms via which their dysregulation occurs, holds significant importance in cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is a paucity of research examining the functions of ITGBL1 in GC. According to a bioinformatics analysis‐based study, it was shown that the overexpression of ITGBL1 had an impact on the overall survival 21 . A study by Yin et al.…”
Section: Discussionmentioning
confidence: 99%